A three‐dimensional high Mach number asymmetric magnetopause model from global MHD simulation. Issue 7 (31st July 2015) - Liu, Z.‐Q.; Lu, J. Y.; Wang, C.; Kabin, K.; Zhao, J. S.; Wang, M.; Han, J. P.; Wang, J. Y.; Zhao, M. X.
Abstract: The numerical results from a physics‐based global magnetohydrodynamic (MHD) model are used to examine the effect of the interplanetary magnetic field (IMF), solar wind dynamic pressure, and dipole tilt angle on the size and shape of the magnetopause. The subsolar magnetopause is identified using the plasma velocity and density, the cusps are identified using the thermal pressure, and the whole shape of the magnetopause is determined with the three‐dimensional streamlines traced through the simulation domain. The magnetopause surface obtained from the simulations is fitted with a three‐dimensional surface function controlled by ten configuration parameters, which provide a description of the subsolar magnetopause, the cusp geometry, the flaring angle, the azimuthal asymmetry, the north‐south asymmetry, and the twisting angle of the magnetopause. Effects of the IMF, solar wind dynamic pressure, and dipole tilt angle on the configuration parameters are analyzed and fitted by relatively simple functions. It is found that the solar wind dynamic pressure mainly affects the magnetopause size; the IMF mainly controls the magnetopause flaring angle, azimuthal asymmetry, and twisting angle; and the dipole tilt angle mainly affects the magnetopause north‐south asymmetry and the cusp geometry. The model is validated by comparing with available empirical models and observational results, and it is demonstrated that the new model can describe the magnetopause for typical solar wind conditions. Key Points: Construct an asymmetric three‐dimensional magnetopause model Compare the new model with the empirical models and observation results Investigate the solar wind effect to the size and shape of the magnetopause